Prediksi Cabang Primagama Bermasalah Menggunakan Algorima C4.5 - Andin Eka Safitri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Primagama is one of indonesia largest site preparation hundreds of branches across the country.The number of branches, the audit should investigate the branches and identify troubled bermasalah.cabang branches which are to be avoided by companies to reach its profit goal the company and preventing the regulation made the turn.But the problem is a lot, and it takes time to choose a branch of the audit problems there.This study apply c4.5 to find the decision and the accuracy of a unique dataset obtained.The result of accuracy c4.5 % 98,60 reached in this research.The accuracy is expected to made new predictions kebijakan kebijakan related to the problem.